Usefulness of mean number of adenomas per positive screenee for identifying meticulous endoscopists among those who achieve acceptable adenoma detection rates - Aniwan, Satimai; Vanduangden, Kunvadee; Kerr, Stephen J.; Wisedopas, Naruemon; Kongtab, Natanong; Kullavanijaya, Pinit; Rerknimitr, Rungsun (Endoscopy, 2020)
Background Adenoma detection rate (ADR) is a quality indicator for colonoscopy. However, many missed adenomas have subsequently been identified after colonoscopies performed by endoscopists with ADR ≥ 25 %. Adenomas per positive participant (APP; mean number of adenomas detected by an endoscopist among screenees with positive findings) correlates well inversely with adenoma miss rate. This study aimed to evaluate whether APP added additional information on the detection rate for advanced adenomas (AADR) and proximal adenomas (pADR) and among endoscopists with acceptable ADRs (≥ 25 %).Methods A total of 47 endoscopists performed 7339 screening colonoscopies that were retrospectively reviewed. Using a cutoff APP value of 2.0, endoscopist performance was classified as high or low APP. Endoscopist ADRs were also classified as acceptable (25 % – 29 %), high standard (30 % – 39 %) and aspirational (≥ 40 %). Generalized linear models were used to assess the relationship between AADR or pADR, and ADR and APP, after adjusting for potential confounders.Results After adjusting for endoscopist performance and patient characteristics, endoscopists with high APP had a significant 2.1 percentage point increase in AADR (95 %CI 0.3 to 3.9; P = 0.02) and a 2.1 percentage point increase in pADR (95 %CI – 0.8 to 5.1; P = 0.15) compared to endoscopists with low APP. In total, 11 (24 %), 18 (38 %), and 18 (38 %) endoscopists were classified as having acceptable, high standard, and aspirational ADRs, respectively. APP values higher than the cutoff were found in 18 %, 44 %, and 72 % of endoscopists with acceptable, high standard, and aspirational ADRs, respectively (P = 0.02).Conclusion APP is helpful for identifying more meticulous endoscopists who can detect a greater number of advanced adenomas. Endoscopists who achieved an only acceptable ADR had the lowest APP.